2013
DOI: 10.1016/j.drugpo.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Opposite social gradient for alcohol use and misuse among French adolescents

Abstract: Background: This study investigates the association of the family occupational category (F-OC) with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 77 publications
2
22
0
3
Order By: Relevance
“…This general framework of time‐preference is supported by survey evidence. Moderate cannabis use (a few times per year or per month) is still more frequent among French adolescents from affluent families, while problematic or daily use are concentrated among those from modest backgrounds, as are tobacco and alcohol consumption . A qualitative study among adolescents in Paris showed that the controlled pattern of use by socially advantaged adolescents was linked to their projection into the future, namely their attention to current school performance and to their plans for entering higher education.…”
Section: Discussionmentioning
confidence: 99%
“…This general framework of time‐preference is supported by survey evidence. Moderate cannabis use (a few times per year or per month) is still more frequent among French adolescents from affluent families, while problematic or daily use are concentrated among those from modest backgrounds, as are tobacco and alcohol consumption . A qualitative study among adolescents in Paris showed that the controlled pattern of use by socially advantaged adolescents was linked to their projection into the future, namely their attention to current school performance and to their plans for entering higher education.…”
Section: Discussionmentioning
confidence: 99%
“…However, all the data were adolescent-reported, implying measurement errors that reduce the precision of our estimates. Much previous research has also relied upon adolescents' information about their parents' social standing [12,21,[51][52][53][54][55][56][57], and the reliability of such proxy measures may be questioned. Comparisons of adolescent-and parent-reported data on parents' SES have revealed moderate to very high agreement [58][59][60][61], and the older the adolescents, the higher the concordance [60][61][62].…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…It is not clear, however, whether certain SES dimensions differ systematically from others in this respect. Opposite or very dissimilar social gradients for different measures of adolescent drinking have also been found [11,[17][18][19]21], highlighting the importance of including more than one drinking outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence is even less clear concerning greater family affluence and higher socio-economic status. Some studies found a link to frequent adolescent binge drinking (Elisaus et al, 2015;Huang, Ho, Wang, Lo, & Lam, 2016;Kendler et al, 2014;Melotti et al, 2013), while others did not (Steiner et al, 2014;Tucker et al, 2013), or found an inverse link (Legleye et al, 2013). Kwok and Yuan (2016) conclude from their recent literature review that in developing countries where parents tend to be poorer and less educated adolescents from affluent and educated families show more binge drinking whereas in developed countries the frequency of adolescent binge drinking depends more on the specific behaviours of parents and friends (see below).…”
Section: Prevalence Of Binge Drinkingmentioning
confidence: 99%